Folktales from Australia's children of the world - MacKellar, M. J. R. (Sydney : U. Smith, 1979)
An anthology of thirty-three folktales, legends, and fables from around the world. The stories appear in their native languages with English translations.
Compiled by M.J.R. MacKellar.
Text in English and other languages.
Keywords: Tales